(untitled) (Bangladesh Medical Journal, 2017)
Physician’s documentation has become the critical component in rehabilitation of patients. The scope of Physical Medicine and Rehabilitation (PMR) encompasses more than a single organ system. Attention to the whole person is paramount. The aim of the study was to appraise the disease pattern and demographic information of the patients received outpatient rehabilitation services at the department of PMR, National Institution of Neuroscience and Hospital, Dhaka, Bangladesh. This is a retrospective study carried out for the period of two years July 2013 to June 2015. Total number of patients was 29678, among them 57.02% were male and 42.98% were female. Maximum patients (26.15%) were in age group 41-50 years and in housewife (37.76%) in occupation, where majority (56.33%) of them came from Dhaka city. Regarding disease pattern, 56.32% was neurological, 33.46% was musculoskeletal and 7.25% of patients were suffering from rheumatologic problem. Among leading diseases, largest disease group was stroke (20.02%), 10.48% was non-specific low back pain, 9.92% was Bell’s palsy, 5.35% was lumbar spondylosis, 5.13% was carpal tunnel syndrome, 4.11% was prolapsed lumber inter-vertebral disk (PLID), 3.72% was cerebral palsy. Knowledge about the existing disease pattern and health seeking behavior is essential to provide need based health care delivery to any population. Bangladesh Med J. 2017 Jan; 46 (1): 15-19